2019
DOI: 10.1186/s12885-019-5983-8
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of lncRNA-miRNA-mRNA ceRNA network in squamous cell carcinoma of tongue

Abstract: Background: Numerous studies have highlighted that long non-coding RNAs (lncRNAs) can bind to microRNA (miRNA) sites as competing endogenous RNAs (ceRNAs), thereby affecting and regulating the expression of mRNAs and target genes. These lncRNA-associated ceRNAs have been theorized to play a significant role in cancer initiation and progression. However, the roles and functions of the lncRNA-miRNA-mRNA ceRNA network in squamous cell carcinoma of the tongue (SCCT) are still unclear. Methods: The miRNA, mRNA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
198
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(200 citation statements)
references
References 44 publications
2
198
0
Order By: Relevance
“…Recently, lncRNAs have been widely demonstrated to function as ceRNAs, and to directly interact with the mRNA-binding site in miRNAs to attenuate either the translational suppression or degradation of target mRNAs, thereby increasing the mRNA and protein levels of target genes. 41,62,63 To investigate whether SNHG7 acts as an miRNA sponge, bioinformatic prediction was performed, and the findings indicated that an miR-485-binding site is present in SNHG7. The luciferase reporter and RIP assays confirmed the direct interaction between SNHG7 and miR-485 in cervical cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, lncRNAs have been widely demonstrated to function as ceRNAs, and to directly interact with the mRNA-binding site in miRNAs to attenuate either the translational suppression or degradation of target mRNAs, thereby increasing the mRNA and protein levels of target genes. 41,62,63 To investigate whether SNHG7 acts as an miRNA sponge, bioinformatic prediction was performed, and the findings indicated that an miR-485-binding site is present in SNHG7. The luciferase reporter and RIP assays confirmed the direct interaction between SNHG7 and miR-485 in cervical cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies indicate that lncRNAs located in the cytoplasm exert their effects on human cancers by acting as a ceRNA for miRNAs. [39][40][41] To illustrate the oncogenic mechanisms of SNHG7 action on cervical cancer cells, we first determined the distribution of SNHG7 within HeLa and C-33A cells. The results suggested that SNHG7 was mainly located in the cytoplasm of HeLa and C-33A cells ( Figure 3A), implying that this lncRNA may serve as a ceRNA in cervical cancer cells.…”
Section: The Snhg7 Knockdown Inhibits the Malignant Characteristics Omentioning
confidence: 99%
“…Accumulating evidence has suggested that lncRNAs may serve as ceRNAs to regulate the expression of miRs and mRNAs (25,26). Therefore, the present study aimed to elucidate the mechanism underlying the MIAT/miR-184 axis in NSCLC cells.…”
Section: Miat Promotes the Expression Of Sf1 By Sponging Mir-184 In Hmentioning
confidence: 97%
“…A change in lncRNA expression has been identified in a variety of human cancer types, including gastric cancer (11), thyroid cancer (12), hepatocellular carcinoma (13) and TScc (14). Regarding TScc, recent studies have indicated that numerous lncRNAs are abnormally expressed in this type of tumor and act as either tumor-suppressors or oncogenic RNAs (15,16). The abnormal expression of lncRNAs may contribute toward the malignancy of TScc by affecting a number of malignant characteristics (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%